Application Of The Structural Dynamic Modification (SDM) Method To Reduce Noise And Vibration Of Vehicle Hvac System - Md Isa, Mohamad Syazwan (Universiti Sains Malaysia, 2018)
Heating, ventilating and air-conditioning (HVAC) system represents a major source in vehicle noise and vibration that contribute a negative effect on the acoustical environment. The operating system itself have produce a significant vibration which subsequently produced an unwanted noise. Noise is amplified when the vibration of components transferred to other components and excites its natural frequency. Natural frequency of a components is depending on its mass and stiffness and can be modified by these two parameters. This study is focusing on the specific HVAC noise and vibration reduction by implementing structural dynamic modification (SDM) method to one of the component involved. The lab-scale of HVAC system is set up to represent the actual HVAC system at the vehicle level. Noise and vibration of HVAC system in vehicle and system levels are measured and compared. From this data, the Dynamic Vibration Absorber (DVA) is designed and applied for a specific component of the HVAC system. The results show that, the natural frequencies of component have been shifted which resulting a wide effective frequency range of 100-500 Hz. The effect of DVA also been observed for the operating HVAC system whereby a significant vibration attenuation has been achieved for operating frequency range of 100-300 Hz.